Collateral hydrogenation over proton-conducting Ni/BaZr0.85Y0.15O3-delta catalysts for promoting CO2 methanation - Choi, Sungjun; Choi, Sung Min; Yoon, Kyung Joong; Son, Ji-Won; Lee, Jong-Ho; Kim, Byung-Kook; Sang, Byoung-In; Kim, Hyoungchul (ROYAL SOC CHEMISTRY, 2018)
Despite the importance of CO2 methanation for eco-friendly carbon-neutral fuel recycling, the current technologies, relying on catalytic hydrogenation over metal-based catalysts, face technological and economical limitations. Herein, we employ the steam hydrogenation capability of proton conductors to achieve collateral CO2 methanation over the Ni/BaZr0.85Y0.15O3- catalyst, which is shown to outperform its conventional Ni/Al2O3 counterpart in terms of CH4 yield (8% higher) and long-term stability (3% higher for 150 h) at 400 degrees C while exhibiting a CH4 selectivity above 98%. Moreover, infrared and X-ray photoelectron spectroscopy analyses reveal the appearance of distinct mobile proton-related OH bands during the methanation reaction.
Keywords: CARBON-DIOXIDE; BARIUM ZIRCONATE; METAL-CATALYSTS; NI; PERFORMANCE; STABILITY; TEMPERATURE; BEHAVIOR; RU; IR